2022
DOI: 10.1039/d2cc02237k
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation, delamination, and oxidation stability of molten salt etched Nb2CTz MXene nanosheets

Abstract: Despite numerous prior reports of molten salt etching of MAX phases, few of these reports achieved water-dispersible MXene nanosheets, and none for Nb-based MXenes. Here we demonstrate the synthesis and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…This propensity to oxidize is affected by the structure of the MXene nanosheet itself. It has been demonstrated that MXenes with a higher value of n in their general formula M n +1 X n T z are more stable. ,, Sang et al reported that harsh etching conditions such as the use of concentrated HF results in defects on the surface of MXenes . These defects act as nucleation sites for degradation reactions.…”
Section: Challenge Of Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…This propensity to oxidize is affected by the structure of the MXene nanosheet itself. It has been demonstrated that MXenes with a higher value of n in their general formula M n +1 X n T z are more stable. ,, Sang et al reported that harsh etching conditions such as the use of concentrated HF results in defects on the surface of MXenes . These defects act as nucleation sites for degradation reactions.…”
Section: Challenge Of Degradationmentioning
confidence: 99%
“…19 However, Arole et al has successfully obtained colloidally stable Ti 3 C 2 T z nanosheet dispersions by adding −OH terminal groups via a potassium hydroxide (KOH) wash, which holds promise for scaling up this technique. 20,21 ■…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the few-layered MXenes nanosheets can be obtained by ultrasonic and centrifugation processing [151,152]. Nevertheless, MXenes prepared by Lewis acidic etching method fail to be terminated by -OH functional group, which greatly decreases their hydrophilicity [153][154][155]. Therefore, it is difficult to uniformly disperse the obtained MXenes in water to form stable colloidal solution, which greatly reduces the delamination efficiency, thus exhibiting a low yield of few-layered and single-layered nanosheets.…”
Section: Delamination Of Multi-layered Mxenesmentioning
confidence: 99%
“…19 Thus, molten salt etching avoids the hazards associated with acid etching and allows for better control over the terminal group distribution of MXenes. [20][21][22] Despite the extraordinary potential of MXenes, degradation remains an issue which affects the shelf-life of MXenes. Many studies have investigated factors such as pH, temperature, and oxygen responsible for the degradation of MXenes.…”
Section: Introductionmentioning
confidence: 99%